Information and communication technology in the lives of forcibly displaced persons in Kenya - Mirko Eppler; Stella Gaetani; Francy Köllner; Jana Kuhnt; Charles Martin-Shields; Nyat Mebrahtu; Antonia Peters; Carlotta Preiß (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
This report examines how forcibly displaced persons use information and communication technologies (ICTs) in Kenya. Focusing on the role and potential of ICT with regard to mobility and inclusion, this paper studies the needs of forcibly displaced persons and seeks to understand how technology could help to meet these needs. The study identifies success factors concerning the deployment of ICT services, which potentially support the lives of forcibly displaced persons. Based on this analysis, we formulate policy recommendations for organisations who want to deploy ICT services for forcibly displaced persons in Kenya. Since living conditions and access to technology differ in urban, rural and camp environments, the research was conducted in Nairobi, the Tana Delta County and Kakuma Refugee Camp. Our results are based on data collected through a mixed-method approach. Qualitative, semi-structured interviews were conducted with 90 forcibly displaced persons in Nairobi, Kakuma Refugee Camp and the Tana Delta County. Twenty-four organisations providing ICT services in Kenya were interviewed to provide a practitioners' perspective. The creation of the interview guides and the codebook for the analysis were developed based on the e-governance framework developed by Verdegem and Verleye, who have identified important conditions for a successful uptake of ICT services, namely awareness, perception, access and usability. [...]
Keywords: 330; Flüchtlinge; Informationstechnik; Kenia